2006
DOI: 10.1038/sj.gt.3302792
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TNFα, a determinant of acute toxicity associated with systemic delivery of first-generation and helper-dependent adenoviral vectors

Abstract: Understanding the determinants of the host innate immune response to systemic administration of adenoviral (Ad) vectors is critical for clinical gene therapy. Acute toxicity occurs within minutes to hours after vector administration and is characterized by activation of innate immune responses. Our data indicate that in mice, indicators of vector toxicity include elevations of cytokine levels, liver transaminase levels and thrombocytopenia. To discern potential targets for blunting this host response, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In this study recombinant adenovirus was injected intramuscularly; no decrease in platelet counts was observed, nor was the prothrombin time (PT) affected. Similar to many previous findings in mice and rhesus monkeys (Schnell et al, 2001;Varnavski et al, 2002Varnavski et al, , 2005Mane et al, 2006), intramuscularly administered recombinant adenovirus induced a transient decrease in WBC counts in the three Ad/hIFN-␥-treated groups in this study.…”
Section: Long-term Toxicity Of Ad/hifn-␥ In Primates 835supporting
confidence: 91%
“…In this study recombinant adenovirus was injected intramuscularly; no decrease in platelet counts was observed, nor was the prothrombin time (PT) affected. Similar to many previous findings in mice and rhesus monkeys (Schnell et al, 2001;Varnavski et al, 2002Varnavski et al, , 2005Mane et al, 2006), intramuscularly administered recombinant adenovirus induced a transient decrease in WBC counts in the three Ad/hIFN-␥-treated groups in this study.…”
Section: Long-term Toxicity Of Ad/hifn-␥ In Primates 835supporting
confidence: 91%
“…The complement branch of the innate immune system appears to play a larger role than just vector opsonization and clearance, studies have shown that complement deficient C3-knockout (KO) mice are defective in the induction of a number of cytokines including CXCL-1, IL-5, G-CSF, GM-CSF, and IL-6 [Kiang et al, 2006]. TNFα also appears to be a modulator of acute toxicity as TNFα-deficient mice display decreased levels of IL-6 and reduced thrombocytopenia in response to Ad vector [Mane et al, 2006].…”
mentioning
confidence: 99%
“…Thus, monitoring every amplification passage allows a better control over the production process. The existing protocols for HC-Ad production are ambiguous with respect to the number of passages that should be performed before starting a largescale preparation [16,23]. In our hands, eight passages were found to be optimal for large-scale preparation.…”
Section: Discussionmentioning
confidence: 88%